2010
DOI: 10.1007/s11947-009-0312-x
|View full text |Cite
|
Sign up to set email alerts
|

Spray Drying Yogurt Incorporating Hydrocolloids: Structural Analysis, Acetaldehyde Content, Viable Bacteria, and Rheological Properties

Abstract: Hydrocolloids and some of their mixtures were used to prepare spray-dried yogurt. Acetaldehyde retention and microbial viability were evaluated. Morphology was examined by scanning electron microscopy and the yield stress was evaluated, to assess the damage to the microstructure by the drying process. The yield stress displayed a significant irreversible decrease after spray drying and micrographs indicate that the microstructure of the yogurt was severely damaged by the drying process. Micrographs indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 20 publications
2
17
0
1
Order By: Relevance
“…Microencapsulation with alginate improved viability of combined selected probiotic organisms by 0.31 log in freeze-dried yoghurt stored at 21°C (Capela et al, 2006). In another study, microbial viability was enhanced significantly using pectin as an encapsulating agent (Rascon-Diaz et al, 2012). In a separate study, alginate combined with gellan gums improved the viability of lactic acid bacteria through microencapsulation (Totosaus et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microencapsulation with alginate improved viability of combined selected probiotic organisms by 0.31 log in freeze-dried yoghurt stored at 21°C (Capela et al, 2006). In another study, microbial viability was enhanced significantly using pectin as an encapsulating agent (Rascon-Diaz et al, 2012). In a separate study, alginate combined with gellan gums improved the viability of lactic acid bacteria through microencapsulation (Totosaus et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Gums, like other polysaccharides, are capable of enhancing viability and enzyme hydrolysis (Corona-Hernandez et al, 2013). However, very few studies have been carried out using gums as prebiotics to enhance the viability and b-galactosidase activity of probiotic microorganisms (Rascon-Diaz et al, 2012;Totosaus et al, 2013). Therefore, it is important to identify gums that could be used as functional ingredients to improve viability and enhance b-galactosidase levels to support the alleviation of lactose intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…bulgaricus and Streptococcus thermophilus are frequently used together as a starter culture; during yoghurt fermentation, they generate many metabolic products, including lactic acid, which contribute to the flavour of the resulting yoghurt (Rascón‐Díaz et al . ). Lactobacillus delbrueckii subsp.…”
Section: Introductionmentioning
confidence: 97%
“…Hydrocolloids are important in maintaining desired texture of fruit leathers. They have been used as gelling or thickening agents capable of binding water molecules, thereby enhancing the desired textural properties of foodstuffs (Rascón-Díaz et al, 2012) Instrumental textural characteristics of fruit leather are measured to match with the desired characteristics when different types of hydrocolloids are used (Gujral and Brar, 2003). Instrumental Texture Profile Analysis showed that high water content increased cohesiveness and decreased springiness of pear fruit leather (Huang and Hsieh, 2005;CheMan and Taufik, 1995).…”
Section: Introductionmentioning
confidence: 99%